Comparison of different methods to face the huge increase in future load in power distribution network - Salam Bnyan Abood; Thamir M. Abdul Wahhab (Bulletin of Electrical Engineering and Informatics, 2022)
The main challenge of present distribution networks is the huge increase in demand for electricity especially in city center where the demand is increasing vertically for the same geographical area. This work presents the analyses of 5-Mail distribution network in Basra City/Iraq with conventional system 33/11/0.416 kV, at future load by estimating the increase in load 10 years later. The network is analyzed in terms of voltage drop, power losses, and the feeder loading. To improve the network the 33/11/0.416 kV system is re-analyzed at the expected future load using the optimal reconfiguration of the network or adding capacitor placement to reduce losses and voltage drop. The results of these methods are compared with the results of the network re-analyzed using the proposed 33/0.416 kV system at future load. The results show that the proposed method of upgrading the voltage level of distribution network is the best solution. The GIS software is used to locate the distribution transformers and lying of the underground cables. CYME software is used to simulate the electric distribution system and conduct the load flow and other analyses.The GIS software is used to locate the distribution transformers and lying of the underground cables. CYME software is used to simulate the electric distribution system and conduct the load flow and other analyses.